Combination among VEP, OCT and TCD data in patients with relapsing-remitting multiple sclerosis during attack-free period - Tekgol Uzuner, Gulnur; Ozer, Ahmet; Uzuner, Nevzat (International journal of neuroscience, 2025)
Multiple sclerosis (MS) is characterized by inflammation, demyelination, glial cell pathology and axonal injury in the central nervous system, and also progressive axonal loss of the optic nerve in cases with optic neuritis (ON). The previous transcranial Doppler (TCD) investigations suggest cortical hyperreactivity in patients with relapsing-remitting Multiple sclerosis (RRMS). We investigated the effect of ON involvement on visual reactivity. One hundred thirty patients with RRMS during attack-free period and 12 healthy subjects were enrolled to the study. Visual evoked potential (VEP), optic coherence tomography (OCT) and TCD examinations of all subjects were performed. Cerebrovascular reactivity measured with breath holding (BH) test was found to be normal. VEP amplitude, visual reactivity and peripapillary retinal nerve fibre layer (pRNFL) measurements were found to be low in patients with ON involvement, whereas VEP latencies were long. Visual reactivity was negatively correlated with VEP amplitude and RFNL measurements, and positively correlated with VEP latency. The present study supports that cerebrovascular reactivity is preserved in patients with RRMS except for attacks, and neurovascular reactivity is increased in patients without ON involvement.